Flour from the Morama bean : composition and sensory properties in a Botswana perspective - Mmonatau, Yvonne (Stellenbosch : University of Stellenbosch, 2006)
Thesis (Msc Food Sc (Food Science))--University of Stellenbosch, 2005.